2022
DOI: 10.1073/pnas.2108935119
|View full text |Cite
|
Sign up to set email alerts
|

The embryonic node behaves as an instructive stem cell niche for axial elongation

Abstract: In warm-blooded vertebrate embryos (mammals and birds), the axial tissues of the body form from a growth zone at the tail end, Hensen’s node, which generates neural, mesodermal, and endodermal structures along the midline. While most cells only pass through this region, the node has been suggested to contain a small population of resident stem cells. However, it is unknown whether the rest of the node constitutes an instructive niche that specifies this self-renewal behavior. Here, we use heterotopic transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 58 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…This approach has the additional advantage of being compatible with live imaging approaches, unlike post-fixation staining (e.g., quail-chick chimeras). A particularly impressive use of the GFP transgenic chicken embryos for fate mapping is described by Solovieva et al [ 2 ]. The Hensen’s node fate map [ 39 ] was revisited using single cell grafts to define the location of self-renewing stem cells, resulting in their precise localisation to the posterior portion of the node [ 2 ].…”
Section: Cell Addition As An Essential Tool In Experimental Embryologymentioning
confidence: 99%
“…This approach has the additional advantage of being compatible with live imaging approaches, unlike post-fixation staining (e.g., quail-chick chimeras). A particularly impressive use of the GFP transgenic chicken embryos for fate mapping is described by Solovieva et al [ 2 ]. The Hensen’s node fate map [ 39 ] was revisited using single cell grafts to define the location of self-renewing stem cells, resulting in their precise localisation to the posterior portion of the node [ 2 ].…”
Section: Cell Addition As An Essential Tool In Experimental Embryologymentioning
confidence: 99%
“…Another well characterized role of the node is its cellular contribution to axial (notochord, floorplate) and paraxial (somite) tissues and definitive gut endoderm ( Rosenquist, 1966 , 1983 ; Schoenwolf et al., 1992 ; Selleck and Stern, 1991 ; Spratt, 1955 ). More recently it has also been shown to act as a niche for resident axial stem cells in chick ( Solovieva et al., 2022 ), a novel role which we will discuss in more detail.…”
Section: Role Of the Nodementioning
confidence: 99%
“…While many cells leave the node to give rise to axial and paraxial structures, some cells remain resident within the node, regressing node and tailbud; we will refer to these as ‘resident cells’ or cells with ‘resident behaviour’. From the collective point of view of the cell population that makes up these structures, resident behaviour in the node, regressing node and tailbud has been demonstrated through homotopic grafts ( Cambray and Wilson, 2007 ; Catala et al., 1995 , 1996 ; McGrew et al., 2008 ), electroporation ( Mathis et al., 2001 ) and DiI labelling ( Knezevic et al., 1998 ; Selleck and Stern, 1991 ; Solovieva et al., 2022 ; Wilson and Beddington, 1996 ). Tracking cells and their descendants from sub-regions of the regressing node and tailbud has revealed that longer term resident cells reside only in the posterior regions of the regressing node ( Cambray and Wilson, 2007 ; Solovieva et al., 2022 ; Wymeersch et al., 2019 ), and in the chordoneural hinge (CNH) and dorsal part of the posterior tailbud ( Cambray and Wilson, 2002 ; McGrew et al., 2008 ) ( Fig.…”
Section: Role Of the Nodementioning
confidence: 99%
See 2 more Smart Citations